PHYTOCHEMICAL INVESTIGATION AND IN VITRO EVALUATION OF LANTANA CAMARA SEED EXTRACTS ON SELECTED HUMAN PATHOGENIC BACTERIA - AMUTHA.S, (International Journal of Pharma and Bio Sciences, 2014)
Lantana camara Linn is an important weed with a vast array of medicinal uses. In this study, antimicrobial activities of methanol, chloroform, acetone, petroleum ether and hexane extracts of L. camara seed was investigated by using Agar Well Diffusion Method. This activity was tested against four human pathogenic bacteria Staphylococcus aureus, Pseudomonas aeruginosa, Proteus vulgaris and Escherichia coli. The extracts were used in three different concentrations (75,150 and 250 ug/ml). Among the extracts, methanolic extract of Lantana camara seed showed maximum inhibition against S. aureus, P.aeruginosa and E. coli and no inhibitory against P. vulgaris. Similarly the acetone extracts of L.camara seed also found to have enormous inhibition against S.aureus, P. vulgaris and lesser activity E. coli.. On the other hand, the other extract of chloroform proved to have no antibacterial activity against the bacterial strains used in this study. The result of phytochemical analysis exposes the presence of saponin, reducing sugar, steroids and flavonoids in the seed extract of Lantana camara.